Relationship Between Observed Groundwater and Soil Morphology in the Sand Plain of Central Wisconsin - Shimek, Steven J (University of Wisconsin-Stevens Point, College of Natural Resources, 1977)
The presence of low chroma (1 or 2) mottles is used by many soil scientists as an indication of seasonal saturation. The Friendship series of central Wisconsin is seasonally saturated within 1.5 m of the soil surface, however, low chroma mottles do not exist within the profile. Also, many areas within central Wisconsin have been drained through channelization of stream downcutting. A method of determining newly attained high groundwater levels has not been developed and the persistance of relic mottles is largely unknown. Groundwater levels and soil observations were made in Friendship soils in an area of natural and altered drainage to determine the relationship between high groundwater levels and soil morphology. The general area investigated is located at the northern extent of the central Wisconsin •sand Plains• in southeast Wood County. The pH, temperature, oxygen, iron and manganese content of the groundwater was measured to determine the origin of certain soil features such as mottles, nodules and cementation. It was found that in areas of natural drainage the upper level of mottling is associated with high groundwater levels. Iron and manganese nodules and cementation may or may not be correlated with the high groundwater level. In areas of altered drainage, cementation and an increase of manganese nodules may indicate new high groundwater levels. It was determined that iron and manganese in mottles, nodules and cementation was from the groundwater system and not the soil. Persistance of mottling in such soils after an alteration of drainage probably exceeds several thousand years.